Chemical constituents of Bulbophyllum wendlandianum (Kraenzl.) Dammer and their chemotaxonomic significance. (June 2021) - Yu, Jia-Duo; Chen, Ya-Ping; Shao, Ya-Ting; Zhou, Xiao-Rong; Zhao, Xia; Li, Yu-Peng
Abstract: Phytochemical investigation of Bulbophyllum wendlandianum (Kraenzl.) Dammer led to the isolation of twenty-three compounds 1–23 (flavanthrinin 1, coelonin 2, lusianthridin 3, densiflorol B 4, plicatol B 5, batatasin-lll 6, gigantol 7, 5-hydroxy-3, 3′-dimethoxy-2-( p -hydroxybenzyl) bibenzyl 8, 2, 2-dimethyl-5-hydroxy-6-carboxy-7-(2-phenylethyl) 9, tristin 10, p -hydroxybenzyl ethyl ether 11, p -hydroxybenzaldehyde 12, hydroquinone 13, coniferaldehyde 14, p -hydroxybenzyl alcohol 15, 3, 4-dihydroxy benzaldehyde 16, stigmasterol 17, β -sitosterol 18, ergosterol peroxide 19, (+)pinoresinol 20, n-butyl sulfoxide 21, tridec-4E-en-l-yl acetate 22, ethyl linolate 23) including five phenanthrenes 1–5, five bibenzyls 6–10, six phenols 11–16, three sterols 17–19, one lignan 20, one n-butyl sulfoxide 21 and two fatty acids 22–23 . The structures of these compounds were elucidated by spectroscopic analyses. This is the first report of isolation of compounds 1–23 from Bulbophyllum wendlandianum and compounds 8–9, 11, 13, 15–16 and 19–23 within genus Bulbophyllum . Compound 21 is a new natural product, isolated from a natural source for the first time. Furthermore, the chemotaxonomic significance of the isolates was also discussed. Graphical abstract: Image 1 Highlights: A phytochemical investigation of Bulbophyllum wendlandianum has been carried out. Twenty-three compounds (1–23) were first isolated from Bulbophyllum wendlandianum. Eleven compounds were first isolated from genus Bulbophyllum. N-butyl sulfoxide (21) is a new natural product, isolated from a natural source for the first time. These compounds provide evidence for chemotaxonomic studies of Bulbophyllum wendlandianum and genus Bulbophyllum.